2011
DOI: 10.1124/jpet.110.175851
|View full text |Cite
|
Sign up to set email alerts
|

Genistein, Resveratrol, and 5-Aminoimidazole-4-carboxamide-1-β-d-ribofuranoside Induce Cytochrome P450 4F2 Expression through an AMP-Activated Protein Kinase-Dependent Pathway

Abstract: Activators of AMP-activated protein kinase (AMPK) increase the expression of the human microsomal fatty acid -hydroxylase CYP4F2. A 24-h treatment of either primary human hepatocytes or the human hepatoma cell line HepG2 with 5-aminoimidazole-4-carboxamide-1-␤-D-ribofuranoside (AICAR), which is converted to 5-aminoimidazole-4-carboxamide-1-␤-D-ribofuranosyl 5Ј-monophosphate, an activator of AMPK, caused an average 2.5-or 7-fold increase, respectively, of CYP4F2 mRNA expression but not of CYP4A11 or CYP4F3, CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…2A, the lower panel). Additionally, the effect of WS010117 on AMPK activation was much more robust than the effect induced by AICAR, a commonly used AMPK activator (Hsu et al, 2011). The effect observed following treatment with 1 μM WS010117 was comparable to treatment with 1 mM AICAR, as determined by the SAMS peptide assay (Fig.…”
Section: Ws010117 Activates Ampk In Hepg2 Cellsmentioning
confidence: 68%
See 1 more Smart Citation
“…2A, the lower panel). Additionally, the effect of WS010117 on AMPK activation was much more robust than the effect induced by AICAR, a commonly used AMPK activator (Hsu et al, 2011). The effect observed following treatment with 1 μM WS010117 was comparable to treatment with 1 mM AICAR, as determined by the SAMS peptide assay (Fig.…”
Section: Ws010117 Activates Ampk In Hepg2 Cellsmentioning
confidence: 68%
“…Compound C is a well-characterised inhibitor of AMPK (Hsu et al, 2011). Simultaneous treatment with compound C resulted in a substantial reduction of AMPK activation via WS010117 (Fig.…”
Section: Ws010117-mediated Ampk Activation Is Inhibited By Compound Cmentioning
confidence: 96%
“…21,22 Because of its regulatory effects on mTOR, there has been recently an emerging interest on the potential use of AMPK activators as antitumor agents. AICAR and metformin are AMPK activators that exhibit antineoplastic activities and exhibit AMPK-dependent effects, 23,24 although they also have AMPKindependent properties. 25,26 Recent evidence has suggested that AICAR exhibits potent inhibitory effects against different types of leukemia and solid tumor cells in vitro, 25,[27][28][29] including BCR-ABLtransformed cells.…”
Section: Resultsmentioning
confidence: 99%
“…Following incubation of cultures for 24 hours, medium was refreshed 4 hours prior to the treatment of hepatocytes with 800 mM of VPA or 20 mM of 2-ene-VPA, 4-ene-VPA, 3-OH-VPA, 3-keto-VPA or vehicle solvent (dimethylsulfoxide or water). For inhibition experiments, hepatocytes were preincubated with 10 mM Compound C for 30 minutes (Hsu et al, 2011), and 1 mM 1-aminobenzotriazole for 1 hour prior (Bumpus, 2011).…”
Section: Methodsmentioning
confidence: 99%